Decomposition analysis of public health service utilization and health disparities among urban and rural older adult migrants in China - Bo Dong; MengHan Jiang; Jing Zong (Frontiers in Public Health)
BackgroundIn the context of China’s aging population and increasing internal migration, “old age” and “mobility” are the special dual attributes of the older adult migrants, and their utilization of basic public health services and health protection is also a major public health issue. Against the backdrop of growing urban–rural development disparities in China, this study aims to examine the differences in public health service utilization and health status between urban and rural older adult migrants and quantify the contribution of relevant influencing factors.MethodsThis study utilized data from the 2018 China Migrants Dynamic Survey (CMDS). After data cleaning, a final sample size of 4,198 participants was analyzed. Descriptive analysis and chi-square tests were used to examine the distribution of three types of public health services—health education, health record establishment, and family doctor contracting—as well as self-reported health status among urban and rural older adult migrants. Multiple linear regression models were applied to identify factors associated with public health service utilization and health status. Finally, the Blinder–Oaxaca decomposition method was used to quantify the extent to which various factors contributed to urban–rural disparities in health service utilization and health outcomes.ResultsRural older adult migrants exhibited slightly higher utilization rates of public health services—health education, health records, and family doctor contracting—compared to their urban counterparts. However, their self-reported health status was significantly lower (76.88% vs. 79.12%). Regression analysis revealed that age, mobility range, education level, income, health insurance coverage, and geographic region were significant factors influencing both service utilization and health outcomes. Public health service use was positively associated with better health in both urban and rural groups. The Blinder–Oaxaca decomposition indicated that age, mobility range, and household income were the primary contributors to urban–rural disparities in health education; age, mobility range, and region contributed most to differences in health record establishment and family doctor contracting; and family doctor contracting, age, mobility range, and region were key drivers of disparities in health status.ConclusionThere are differences in public health service utilization and health status between urban and rural older adult migrants in China. While rural older adult migrants use public health services at a slightly higher rate, they experience worse health outcomes than their urban counterparts—largely due to socio-economic and regional disparities. Targeted interventions aimed at improving access, enhancing health education, optimizing service delivery, and strengthening policy support are essential to narrowing these urban–rural health gaps and promoting health equity among older adult migrants.